2011
DOI: 10.1111/j.1530-0277.2011.01608.x
|View full text |Cite
|
Sign up to set email alerts
|

The Legacy of Minimum Legal Drinking Age Law Changes: Long‐Term Effects on Suicide and Homicide Deaths Among Women

Abstract: Background Prior to the establishment of the uniform drinking age of 21 in the United States, many states permitted legal purchase of alcohol at younger ages. Lower drinking ages were associated with several adverse outcomes, including elevated rates of suicide and homicide among youth. The objective of this study is to examine whether individuals who were legally permitted to drink prior to age 21 remained at elevated risk in adulthood. Methods Analysis of data from the U.S. Multiple Cause of Death files, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 40 publications
(39 reference statements)
3
39
0
Order By: Relevance
“…If cross-state migration is uncorrelated with MLDA and high school dropout, as we assumed, our estimates likely underestimate the true relationship between permissive MLDA and high school dropout. We have established that this is a reasonable assumption in previous work (Grucza et al, 2012;Norberg et al, 2009).…”
Section: Limitations and Conclusionsupporting
confidence: 58%
See 2 more Smart Citations
“…If cross-state migration is uncorrelated with MLDA and high school dropout, as we assumed, our estimates likely underestimate the true relationship between permissive MLDA and high school dropout. We have established that this is a reasonable assumption in previous work (Grucza et al, 2012;Norberg et al, 2009).…”
Section: Limitations and Conclusionsupporting
confidence: 58%
“…Further, our earlier work suggested that migration would bias our results toward a false-positive result only under very high selective migration: more than 25% (Grucza et al, 2012). Because there was no evidence that any selective migration based on MLDA exposure occurred, it was unlikely that estimating MLDA exposure was a source of confounding for our analyses.…”
Section: Minimum Legal Drinking Age Exposure Codingmentioning
confidence: 88%
See 1 more Smart Citation
“…To the best of our knowledge, no previous study has analyzed the long-term effects of a lowered purchase age (aside from cohort studies with a different focus). 11,12 Lowering the purchase age had no impact on fatal alcohol-involved crashes among drivers aged 18 to 19 years compared with drivers aged 20 to 24 years. Numbers of alcohol-involved fatal crashes were smaller, which may have reduced statistical power.…”
Section: Discussionmentioning
confidence: 95%
“…5--- 10 We could not find any published study reporting the long-term relationships between lowering the legal age limit and harms in which the postlaw change period comprised 10 or more years of data (aside from studies finding cohort effects as affected age groups grew older). 11,12 The minimum legal purchase age for alcohol in New Zealand was lowered from 20 to 18 years 13 on December 1, 1999, providing a context in which to study the longer term effects of such a law change.…”
mentioning
confidence: 99%